Optimization Design of Multi Station Rotary Automatic Turning and Resetting Mechanism - Zhao Haiming; Zhang Linlin; Liao Xiaole (Jixie chuandong)
In order to realize the function of the working station automatic turning and resetting,the multi station rotary automatic turning and resetting mechanism which is powered by cylindrical cam is proposed. Each working station is composed of a crank slider mechanism,the displacement of the slider is controlled by the change of the cam curve which drives the rotation of the crank and completes the turning of the working station.The mathematical model of this mechanism is established,through the variation of the design parameters can meet the requirements of different engineering requirements. In order to research the structure of multi station automatic turning and resetting mechanism fitting the empty request,the case of automatically empty the prefabricated hard cigarette is used as an example. The optimization of the automatic turning and resetting mechanism which is multi- objective is carried out. The minimum cam lift and vertical height,the maximum flip angle are the objective. The independent variables of this optimization are the parameters,such as the length of the crank and the connecting rod,the cam lift and so on. The optimization effect is obvious,and the rationality of the design parameter is verified by the simulation analysis.